3D bulk field theories for 2D non-unitary N $$ \mathcal{N} $$ = 1 supersymmetric minimal models - Seungjoo Baek; Dongmin Gang (Journal of High Energy Physics)
Abstract We propose bulk 3D N $$ \mathcal{N} $$ = 4 rank-0 superconformal field theories, which are related to 2D N $$ \mathcal{N} $$ = 1 supersymmetric minimal models, SM (2, ·) and SM (3, ·), via recently discovered non-unitary bulk-boundary correspondence. The correspondence relates a 3D N $$ \mathcal{N} $$ = 4 rank-0 superconformal field theory to 2D chiral rational conformal field theories. A topologically twisted theory of the rank-0 SCFT supports the rational chiral algebra at the boundary upon a proper choice of boundary condition. We test the proposal by checking several non-trivial dictionaries of the correspondence.